Pengaruh Celebrity Endorser Ria Ricis Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Dengan Brand Image Sebagai Variabel Intervening (Pada Mahasiswa FEB Angkatan 2018 Universitas Islam Malang Pengguna Scarlett Whitening) - Alviana Mariska; N. Rachma; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis research aims to determine and analyze the influence of celebrity endorser and electronic word of mouth on purchasing decisions with brand image as an intervening variable. The population in this study were Faculty of Economic and Business 2018 students at the Islamic University of Malang who used Scarlett Whitening with a total sample of 95 respondents. The data analysis method used in this study is a quantitative method with path analysis techniques. Sampling technique with non-probability sampling technique with purposive sampling method. The results show that celebrity endorser did not have a direct effect on brand image, while eWOM had a direct effect on brand image. Celebrity endorsers, eWOM and brand image have a direct effect on purchasing decisions, brand image cannot mediate celebrity endorsers on purchasing decisions but brand image can mediate eWOM on purchasing decisions. Keywords: Celebrity Endorser, eWOM, Brand Image, Purchase Desicions